THE EFFECTS OF OPEN FIELD EXPOSURE ON THE ANXIETY AND LOCOMOTIVE BEHAVIOR OF ADULT MALE WISTAR RATS IN ELEVATED PLUS MAZE - Kumar, Jaya; Hapidin, Hermizi; Get Bee, Yvonne-Tee; Ismail, Zalina (2016)
Anxiety is a multifaceted emotional disorder which requires multiple research models for effective assessment of the condition. Usually, a large number of animals will be used for a single study which will not be reused in other studies. The use of different groups of animals for different aspects of any study may create inter-subject variations that can confound the observed results. Objective of this study is to investigate the effect of pre-exposure to open field (OF) on the anxiety and locomotor behaviors of male adult Wistar rats in elevated plus maze (EPM). We evaluated the effect of pre-exposure in OF on the anxiety and locomotor behaviors of rats at 3 different time intervals. The control group consisted of rats which underwent single exposure in EPM, and the other three groups consisted of rats which underwent a pre-exposure in OF immediately before the EPM session, 2 days before the EPM session, and a week before the EPM session. Our results show that there was no significant effect of OF pre-exposure on the anxiety and the locomotive behavior of rats in EPM at these 3 different intervals. In conclusions, these tests can be conducted successively with minimum time duration in the gap between these two tests.